Human Immunodeficiency Virus Pre-Exposure Prophylaxis Service Program in Sidoarjo Regency: Development, Achievements and Challenges - Unsiyyatul Usriyyah; Arief Hargono (Journal of Public Health for Tropical and Coastal Region, 2026)
Introduction: HIV Pre-exposure Prophylaxis (PrEP) is an additional prevention method for HIV transmission. Sidoarjo Regency, one of the pilot areas for HIV PrEP services in Indonesia, has been providing HIV PrEP services since 2022. In 2022 and 2023, the Sidoarjo Regency did not achieve the targets set by the Indonesian Ministry of Health. This study aimed to provide a comprehensive overview of the implementation of the PrEP program in Sidoarjo Regency.Methods: This evaluation used a descriptive design. The indicators included (1) coverage of HIV-negative individuals among key populations, (2) PrEP initiation coverage, and (3) PrEP uptake coverage. Data were obtained from the National PrEP Information System and in-depth interviews with the program managers. The evaluation also examined input components, including the availability of human resources, funding, and facilities, as well as process components related to service implementation, supervision, and the mechanisms of service delivery.Results: The expansion of PrEP services was conducted by increasing the number of service sites from four in 2022 to 15 in 2024. In addition, PrEP services have been integrated with mobile VCT and community-based referrals. PrEP uptake among key populations has also been studied; however, national initiation targets were achieved only among MSM in 2024.Conclusion: HIV PrEP services must be expanded to provide more options for at-risk individuals. Moreover, the integration of PrEP administration during mobile VCT makes it easier for targets who have no access to health services that provide PrEP